2008
DOI: 10.1007/s00425-008-0727-z
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the response to high-salinity stress in Physcomitrella patens

Abstract: Physcomitrella patens is well known because of its importance in the study of plant systematics and evolution. The tolerance of P. patens for high-salinity environments also makes it an ideal candidate for studying the molecular mechanisms by which plants respond to salinity stresses. We measured changes in the proteome of P. patens gametophores that were exposed to high-salinity (250, 300, and 350 mM NaCl) using two-dimensional gel electrophoresis (2-DE) via liquid chromatography-tandem mass spectrometry (LC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
119
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 46 publications
8
119
0
Order By: Relevance
“…All 71 differentially displayed protein spots were excised from preparative 2-D gels, digested with trypsin, and analyzed through LC-MS/ MS. We searched the amino acid sequences against the databases using the SEQEST software as described before (Wang et al, 2008). All of the differentially expressed proteins could be identified, with just 19 of them categorized as unknown or putative proteins (Table I), and their sequence-matched peptides are shown in Supplemental Table S1.…”
Section: Liquid Chromatography-tandem Mass Spectrometry Protein Identmentioning
confidence: 99%
See 1 more Smart Citation
“…All 71 differentially displayed protein spots were excised from preparative 2-D gels, digested with trypsin, and analyzed through LC-MS/ MS. We searched the amino acid sequences against the databases using the SEQEST software as described before (Wang et al, 2008). All of the differentially expressed proteins could be identified, with just 19 of them categorized as unknown or putative proteins (Table I), and their sequence-matched peptides are shown in Supplemental Table S1.…”
Section: Liquid Chromatography-tandem Mass Spectrometry Protein Identmentioning
confidence: 99%
“…We detected HSP70s as the major HSPs that play a role in the P. patens response to desiccation (Table I) and cold (data not shown). Recently, these proteins have also been shown to be important for high salinity (Wang et al, 2008). Genome analysis has shown that the HSP70 family has expanded to nine cytosolic members in P. patens, whereas all algal genomes sequenced to date encode a single cytosolic HSP70 (Wang et al, 2004).…”
Section: Metabolism Adjustment In Response To Desiccationmentioning
confidence: 99%
“…These proteins are phototropin, myelin basic protein kinase, MCamb1 and MCamb2, 14-3-3 like protein and PpDBF1. [4][5][6][7] Phototropin is the blue light receptor that mediates phototropism, chloroplast relocation and stomatal opening in higher plants. 8 In Physcomitrell patens, phototropin and 14-3-3 proteins may work cooperatively to regulate plasma membrane H + -ATPase and maintain ion homeostasis.…”
Section: Salt Signal Compoments and Transcript Regulationmentioning
confidence: 99%
“…8 In Physcomitrell patens, phototropin and 14-3-3 proteins may work cooperatively to regulate plasma membrane H + -ATPase and maintain ion homeostasis. 4 The 14-3-3 proteins are important eukaryotic regulatory proteins, most of which are involved in cellular signaling pathways. 9 Through regulating the activities of kinases and phosphatase, 14-3-3 proteins integrate themselves into several levels of signal transduction cascades.…”
Section: Salt Signal Compoments and Transcript Regulationmentioning
confidence: 99%
See 1 more Smart Citation